Peranan Volume Usaha Dalam Mencapai Keberhasilan Koperasi - Ubaidillah - AMIK BSI Jakarta (Universitas Bina Sarana Informatika, 2016)
Abstract - Cooperatives have an important role in the economy in Indonesia. Even during an economic crisis where many companies public and private property encountered a problem and many are falling, cooperatives proved capable of sustaining the country's economy. Besides the cooperative development is very helpful in the development of social economy. The development of cooperatives themselves from year to year has increased in terms of quantity, but in terms of quality has decreased. Loss of quality can be seen from the increasing percentage of the number of cooperatives that are not active. Many factors influence the percentage increase in the number of cooperatives that are not active. But one of the factors that influence the development of cooperatives is the volume of business. This study aims to determine the role of business volume in cooperative development. The method used in this research is descriptive qualitative method where data collection techniques used is a literature study. The results showed that the volume of business was instrumental in the development of cooperatives, especially in realizing the independence of the cooperative, the cooperative into a cooperative help achieve healthy, help to achieve success, as well as help in maintaining the activity of cooperatives, especially in terms of financial cooperatives. Keywords: cooperative, business volume, the independence of cooperative Abstrak - Koperasi mempunyai peranan penting dalam perekonomian di Indonesia. Bahkan saat terjadi krisis ekonomi dimana banyak perusahaan milik pemerintah maupun milik swasta mengalami masalah dan banyak yang berjatuhan, koperasi terbukti mampu menopang ekonomi negara. Selain itu pengembangan koperasi sangat membantu dalam pengembangan ekonomi kerakyatan. Perkembangan koperasi sendiri dari tahun ke tahun mengalami kenaikan dari sisi kuantitas, tetapi dari sisi kualitas justru mengalami penurunan. Penurunan kualitas tersebut dapat dilihat dari meningkatnya persentase jumlah koperasi yang tidak aktif. Banyak faktor yang berpengaruh pada peningkatan persentase jumlah koperasi yang tidak aktif tersebut. Tetapi salah satu faktor yang berpengaruh dalam pengembangan koperasi adalah volume usaha. Penelitian ini bertujuan mengetahui peranan volume usaha dalam pengembangan koperasi. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif dimana teknik pengumpulan data yang digunakan adalah literature study. Hasil penelitian menunjukkan bahwa volume usaha sangat berperan dalam pengembangan koperasi terutama dalam mewujudkan kemandirian koperasi, membantu pencapaian koperasi menjadi koperasi sehat, membantu mencapai keberhasilan, serta membantu dalam mempertahankan keaktifan koperasi terutama dari sisi finansial koperasi. Kata kunci: koperasi, volume usaha, kemandirian koperasi